Plant community assembly along a natural metal gradient in central Africa: Functional and phylogenetic approach. (27th November 2019) - Delhaye, Guillaume; Hardy, Olivier J.; Séleck, Maxime; Ilunga wa Ilunga, Edouard; Mahy, Grégory; Meerts, Pierre
Abstract: Questions: Do functional and phylogenetic diversity vary along a natural metal gradient? Do resources acquisition and metal tolerance‐related traits show the same patterns of variation? Is the ability to grow on metal‐enriched soil phylogenetically conserved or the result of functional convergence? Location: Fungurume V hill (10°37′03″ S, 26°17′22″ E), Upper Katanga, Democratic Republic of Congo. Methods: In 21 communities along a natural copper gradient, we quantified the variation of species richness and turnover as well as the phylogenetic diversity. We assessed the variation of three univariate functional indices — community‐weighted mean, functional richness and functional dispersion — for ten functional traits related to resources acquisition, conservation, dispersal and metal tolerance strategy. Results and Conclusions: Along a gradient of increasing soil Cu concentration, we found a decrease in species number and a strong species turnover. On metal‐poor soils, phylogenetic clustering and overdispersion of functional traits indicated selection for certain clades (e.g. Fabaceae) with many different trait combinations suggesting niche partitioning. On metal‐enriched soils, contrary to expectations, we found functional convergence towards trait values associated with rapid resource use, lower stature and smaller seeds in several clades. Conversely, metal tolerance strategy showed a clear overdispersion on metal‐rich soils reflecting the presence of several strategies to cope with the excess of metal in the soil. This suggests that some extreme toxicity gradients, such as this one, do not always impose strong functional convergence towards a stress tolerance strategy, as is often assumed. Abstract : Variation in functional and phylogenetic diversity was explored along a natural soil copper gradient. On metal‐poor soil, we found niche partitioning resulting from competition. On metal‐rich soils, the community showed convergence to a syndrome of fast resource capture and small stature despite phylogenetic overdispersion. In contrast, widely divergent metal tolerance strategies coexist at high copper levels.